Communicational approach of strategy in organizations - Terossi, Karen (Organicom, 2021)
Theoretical and practical reflections, experiences, cases and paths for strategic communication are presented in the book “Strategic and integrated communication: the vision of renowned authors from 5 countries”, which brings texts by researchers and professionals working in this area, from Brazil, Mexico, Chile, Spain and Portugal. And despite the different choices and paths pointed out, the authors have in common the search for a communicational approach to the issue of strategy in organizations. This means, in essence, placing the human being and the relational paradigm at the center of organizational communication management.